Rehabilitation Approaches of a Bangladeshi Boy With Ataxia Telangectasia: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2019)
Ataxia-Telangiectasia (AT) is a rare form of neurodegenerative disorder of hereditary origin. In Bangladesh we don’t have any epidemiological study. Till today there is no gold standard of the diagnosis, further to its wide clinical heterogeneity, it often leads physicians to an incorrect or missed diagnosis. So is the importance of the insight into this disease. We report a 10 years old male child who presented with history of difficulty in posture and walking associated with frequent fever, delayed slurred speech and abnormal eye movements. Physical examination revealed delayed milestones of development involving neck control, sitting, walking, unsteady supported swaying gait and speech language dysfunctions. MRI of brain showed cerebellar atrophy and a raised serum Alfafeto protein level. The child was diagnosed as a case of AT and was presented in a clinical meeting at Bangabandhu Sheikh Mujib Medical University for discussions and further managements including medical rehab. We offered him a course of combined rehabilitation therapy program and discharged home.JCMCTA 2019 ; 30 (1) : 64-67